Global Commodity Markets : Review and Price Forecast - World Bank (World Bank, Washington, DC, 2015)
A companion to Global Development Finance 2009. The slowing of global growth, which preceded the financial crisis by several months, prompted commodity prices to start falling in mid-2008. The eruption of the full-blown crisis and the rapid drop-off in economic activity since September of that year accelerated this process markedly. Demand for most commodities (notably, in high-income industries and in China) slowed or declined, particularly for oil and metals. By December 2008, crude oil prices had dropped to $41 a barrel, down more than 70 percent from the July peaks, while non-energy prices, including food,had declined by nearly 40 percent. Since December, prices have firmed, with crude oil prices up to $69 on average in June 2009, and prices for foods and metals up 22 and 13 percent, respectively.